IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI SISWA KELAS IVB SD KRISTEN 3 EBEN HAEZER SALATIGA - Andi setyawan (Joyful Learning Journal, 2023)
The purpose of this study was to analyze the implementation of differentiated learning for fourth-grade students at SD Kristen 3 Eben Haezer Salatiga. This research used a descriptive-analytic method with a qualitative approach. The research stages consisted of planning, implementation, and reflection. The results of the planning analysis obtained data on learning styles with 44% visual, 22% auditory, and 33% kinesthetic. The implementation of differentiated learning used various methods of material delivery, including videos, teacher explanations, and practice exercises. The response from students showed an 80% satisfaction and enthusiasm because they were able to learn with materials they liked and were capable of, as well as materials preferred by their peers. Additionally, the results of the summative assessment indicated that 77% of students had a good understanding of the material, while the remaining 13% needed further assistance to adjust to their learning abilities.